Highly sensitive and transparent flexible temperature sensor based on nematic liquid crystals. Issue 3 (19th February 2022) - Wu, Keming; Sun, JingJing; Gao, Lin; Xing, Hongyu; Cai, Minglei; Zhao, Tongzhou; Yang, Changyong; Ye, Wenjiang; Kong, Xiangming
ABSTRACT: In this paper, a highly sensitive and transparent flexible temperature sensor fabricated from the polyethylene terephthalate flexible substrate and the nematic liquid crystal (1M0921900-000) is proposed, which simultaneously has low power consumption. Using the relaxation time ( τ = RC ) as an intrinsic variable to characterise temperature, a better linear fitting with temperature can be obtained at low voltage, high precision and more stable temperature monitoring can be achieved. The maximum sensitivity is −4.05%/°C at 0.1 V and 200 Hz. The transmittance of the sensor can reach 62.36–81.13% in the visible light range. Compared with the rigid liquid crystal temperature sensor, the rise time and the decay time of the sensor are reduced by 97.104% and 90.313%, respectively. In addition, it also has good stability, recovery, and durability, which shows potential applicability to electronic skin, prostheses, robots, and biomedical by accurately monitoring the change of external temperature. Graphical abstract: uf0001